Alleviating Soil Fertility Constraints to Increased Crop Production in West Africa 1991
DOI: 10.1007/978-94-011-3224-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating soil fertility constraints to increased crop production in West Africa: The experience in the Sahel

Abstract: Lack of moisture limits crop production in semi-arid west Africa but poor soil fertility is a more serious constraint in the long run. Work done by IFDC and ICRISAT showed that phosphorus is the most limiting nutrient although response by millet to nitrogen when moisture and P are non-limiting can be substantial. A summary of the results of field trials in Niger showed that the sufficiency level for P estimated by regression analysis on the basis of Bray 1 extractable P is 7.9 JAg Pig of soil for 90% of maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 12 publications
5
48
0
1
Order By: Relevance
“…Several authors have reported a challenge of poor soil fertility that farmers in semi-arid areas are facing [153][154][155]. The problem is acute for poor farmers in semi-arid Sub-Saharan Africa countries [151,156,157]. The precision-farming technique referred to as "microdosing" has been developed by experts [158][159][160].…”
Section: Micro-fertilizationmentioning
confidence: 99%
“…Several authors have reported a challenge of poor soil fertility that farmers in semi-arid areas are facing [153][154][155]. The problem is acute for poor farmers in semi-arid Sub-Saharan Africa countries [151,156,157]. The precision-farming technique referred to as "microdosing" has been developed by experts [158][159][160].…”
Section: Micro-fertilizationmentioning
confidence: 99%
“…Because of this, cultivation causes decrease in soil nutrients. Detailed studies on this chemical degradation of the soil (depletion of soil nutrients) and its recovery through fertilization have been conducted by A. Bationo, A. Buerkert, K. Hayashi and others (see Bationo and Mokwunye 1991;Bationo et al 1993;Buerkert et al 2000;Hayashi et al 2008;etc.). Additionally, Nakamura et al (2010) have published work on the depletion of soil organic matter as a result of cultivation and its recovery through the application of organic amendment.…”
Section: Preface -The Least Developed Countries In the Southern Saharmentioning
confidence: 99%
“…As local farmers in Niger have limited access to outsourcing for soil fertility management 4,32 , judicious utilization of their finite resources is crucial. Precision agriculture is one way to use limited resources efficiently through minimal inputs for maximal outputs from crop production 11,29 .…”
Section: Validation Of Indigenous Knowledge To Manage Soil Fertilitymentioning
confidence: 99%